Diagnostic accuracy of a milk pregnancy-associated glycoprotein ELISA accounting for day since last breeding for pregnancy detection in Holstein cows - Simon Dufour; Jean Durocher; Geoffrey Fosgate; Peter C. Irons; Stephen J. LeBlanc; Elouise Molgat (Preventive Veterinary Medicine, 2026)

Post-vaccination serological status predicts protection against heterologous SAT1 foot-and-mouth disease virus challenge in goats - Geoffrey T. Fosgate; Dricus R. Oerlemans; LaToya Seoke; Pamela A. Opperman; David D. Lazarus; Moses Gobiye; Livio Heath (Preventive Veterinary Medicine, 2026)

A Bayesian latent class estimation of the diagnostic accuracy of clinical examination and laboratory assays to identify bovine ephemeral fever virus infection in South African cattle - Miemie Grobler; Geoffrey T. Fosgate; Robert Swanepoel; Jan E. Crafford (Preventive Veterinary Medicine, 2025)

Assessment of communal farmers’ knowledge of foot-and-mouth disease (FMD) within the FMD protection zone with vaccination of Limpopo and Mpumalanga Provinces, South Africa - Kibambe D. Kiayima; Eric Etter; Petronella Chaminuka; Alexis Delabouglise; Geoffrey T. Fosgate (Preventive Veterinary Medicine, 2025)

Bovine cysticercosis epidemiology and the economic impact of the triceps brachii incision in a South African export abattoir - Matthys Uys; Geoffrey T. Fosgate; Alessandro Seguino (Preventive Veterinary Medicine, 2023)

Preliminary validation of a single-spot version of a solid-phase competition ELISA for the detection of southern African territories foot-and-mouth disease serotype exposure in goats - Moses Gobiye; Geoffrey T. Fosgate; Livio Heath; David D. Lazarus; LaToya Seoke; Pamela A. Opperman (Small Ruminant Research, 2023)

The seroprevalence of African horse sickness virus, and risk factors to exposure, in domestic dogs in Tshwane, South Africa - Josef Hanekom; Baratang A. Lubisi; Andrew Leisewitz; Alan Guthrie; Geoffrey T. Fosgate (Preventive Veterinary Medicine, 2023)

The knowledge, attitudes, and practices of smallholder cattle farmers concerning the epidemiology of bovine fasciolosis in the North West Province, South Africa - Sunday Charles Olaogun; Geoffrey Theodore Fosgate; Charles Byaruhanga; Munyaradzi Christopher Marufu (Tropical Animal Health and Production, 2023)
Bovine fasciolosis has negative impacts on cattle production worldwide, more so on the African continent and especially in smallholder farming areas with limited level of awareness. A cross-sectional questionnaire-based survey was conducted to investigate the knowledge, attitudes, and practices concerning bovine fasciolosis among smallholder cattle farmers in the North West Province of South Africa. A total of 153 farmers were interviewed from three villages of the Moretele Local Municipality in Bojanala District. The majority of respondents were male (84%) farm owners (81%) that had low education levels (56% primary school or less) and employed extensive cattle management systems (84%). A large number of farms lacked infrastructure including calving pens (88%), restraining equipment (85%), and weight determination equipment (92%) while sourcing drinking water for cattle from rivers or dams (58%). No evaluated factors were significantly associated with a positive fasciolosis epidemiological knowledge score. However, education level ( P = 0.046), some cattle breeds ( P = 0.022), and management system ( P < 0.001) of the smallholder farmers were associated with a positive practice score concerning bovine fasciolosis prevention. We therefore recommend that education programs be introduced that focus on the mode of transmission, risk factors, zoonotic importance, and practices associated with the prevention and control of bovine fasciolosis.

Spatial distribution of foot-and-mouth disease (FMD) outbreaks in South Africa (2005–2016) - Mohamed Mahmoud Sirdar; Geoffrey Theodore Fosgate; Belinda Blignaut; Lucas R. Mampane; Oupa Boetie Rikhotso; Ben Du Plessis; Bruce Gummow (Tropical Animal Health and Production, 2021)

Rehabilitation method affects behavior, welfare, and adaptation potential for subsequent release of orphaned white rhinoceros - María C. Fàbregas; Geoffrey T. Fosgate; André Ganswindt; Henk Bertschinger; Markus Hofmeyr; Leith C. R. Meyer (acta ethologica, 2020)

Behavioral and adrenocortical responses of captive white rhino adolescents to the introduction of a new calf - María Cayetana Fàbregas; André Ganswindt; Geoffrey T. Fosgate; Henk J. Bertschinger; Leith C. R. Meyer (acta ethologica, 2019)

Effect of different levels of dietary nitrogen supplementation on the relative blood urea nitrogen concentration of beef cows - Takula Tshuma; Geoffrey Theodore Fosgate; Robyn Hamman; Dietmar Erik Holm (Tropical Animal Health and Production, 2019)

Pre-breeding blood urea nitrogen concentration and reproductive performance of Bonsmara heifers within different management systems - Takula Tshuma; Dietmar Erik Holm; Geoffrey Theodore Fosgate; Dirk Cornelius Lourens (Tropical Animal Health and Production, 2014)

Association between ecological factors and the presence of Rhipicephalus (Boophilus) microplus larvae in Puerto Rico - José Urdaz-Rodríguez; Geoffrey Fosgate; A. Rick Alleman; Owen Rae; Arthur Donovan; Michael Binford; Alexis Zaragoza; Pedro Melendez (Experimental and Applied Acarology, 2012)

Brucellosis in domestic water buffalo (Bubalus bubalis) of Trinidad and Tobago with comparative epidemiology to cattle - Geoffrey T. Fosgate; Michael D. Diptee; Anil Ramnanan; Abiodun Adewale Adesiyun (Tropical Animal Health and Production, 2011)

Virulence of Brucella abortus isolated from cattle and water buffalo - Abiodun A. Adesiyun; Geoffrey T. Fosgate; Ravi Seebaransingh; Gabriel Brown; Simone Stoute; Alva Stewart-Johnson (Tropical Animal Health and Production, 2011)

Environmental risk factors for equine West Nile virus disease cases in Texas - Michael P. Ward; Courtney A. Wittich; Geoffrey Fosgate; Raghavan Srinivasan (Veterinary Research Communications, 2009)